Genetic determinants of TAC chemotherapy response in triple negative breast cancer patients - Aziz, Ahmad Aizat Abdul (2018)
Triple negative breast cancer (TNBC), one of the breast cancer subtypes is characterised by aggresive phenotype, high rates of recurrence and poor prognosis and is an important clinical challenge due to lack of specific targeted therapy. Although, TNBC patients are treated with taxane, adriamycin and cyclophosphamide (TAC) chemotherapy regimen, drug resistance and tumour recurrence are major obstacles in TNBC treatment. Reliable prognostic marker of TNBC remains elusive. The present study was undertaken to investigate the impact of selected SNPs of CYP1B1 142 C>G (rs10012), 4326 C>G (rs1056836) and 4390 A>G (rs1800440), CYP3A4 878 T>C (rs28371759), CYP3A5 6986 A>G (rs776746), ABCB1 1236 C>T (rs1128503), 2677 G>T/A (rs2032582) and 3435 C>T (rs1045642) and their respective gene expressions as well as expression levels of selected miRNAs (miR-21, miR-27b, miR-34a, miR- 182, miR-200c and miR-451) in modulating TAC chemotherapy response and treatment outcome in TNBC patients. Seventy six (76) blood samples and 41 match paired FFPE tissues blocks available from the same group of clinically and histopathologically confirmed TNBC patients, who had undergone surgery and completed six cycles of TAC chemotherapy regimen were included in the study. DNA (blood samples) and total RNA (FFPE tissues blocks) were extracted. Genotyping was carried out using PCR-RFLP and AS-PCR methods followed by DNA sequencing. mRNA and miRNA expression levels were determined using qRT-PCR. The treatment response and disease outcome of the patients were evaluated after completion of chemotherapy. Based on chemotherapy response, patients werecategorized into chemoresistant and chemoresponse groups. In genetic association analysis, homozygous variant genotype and variant allele of CYP1B1 4326 C>G and ABCB1 3435 C>T polymorphisms, combination of CYP1B1 142 GG + CYP3A4 878 TT and CYP1B1 4326 GG + ABCB1 1236 CT genotypes, CYP1B1 4326G/142C, ABCB1 3435T/2677G/1236T and ABCB1 3435T/2677T/1236T haplotypes were associated with significantly higher risk for chemoresistance. Whereas, CYP1B1 142 CG genotype was significantly associated with good chemoresponse. For mRNA and miRNA expression levels analysis, high expression level of CYP1B1 was significantly associated with chemoresistance. Moreover, up regulation of miR-21 and miR-182 were found to be associated with increased risk of relapse and to be a prognosis factor in TNBC patients undergoing TAC chemotherapy. On the other hand, CYP1B1 142 CG genotype was found to be a good prognostic factor for predicting survival in TNBC patients. Thus, CYP1B1 4326 GG, ABCB1 3435 TT genotypes, high CYP1B1 mRNA expression level and up regulation of miR-21 and miR-182 expression levels emerged as genetic determinants of TAC chemotherapy response in TNBC patients. These genetic determinants could be considered as potential biomarkers that might help the clinician, especially in predicitng recurrence risk and/or prognosis and thus improve management of TNBC patients.